2021
DOI: 10.4103/jehp.jehp_871_20
|View full text |Cite
|
Sign up to set email alerts
|

The opportunities and challenges of using mobile health in elderly self-care

Abstract: Population aging is a phenomenon expanding around the world and will be increase the incidence of chronic diseases and health costs. This study was conducted according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA). A comprehensive literature search was performed on 4 databases (Web of Science, PubMed, Science Direct, and ProQuest) for English language studies from January 1, 2000, to December 31, 2019. The keywords used to extract relevant contents were “e-health,” “Elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…The Poor functionality of phone system was evidenced among several respondents and yet proper functionality of a technology device is an important factor in determining adoption by an individual. In studies conducted by Rapudo (2013) and Yang (2022) show functionality of a technology or mobile device is also a determinant of adoption despite the fact that it is always not observed (Rapudo, 2013;Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Poor functionality of phone system was evidenced among several respondents and yet proper functionality of a technology device is an important factor in determining adoption by an individual. In studies conducted by Rapudo (2013) and Yang (2022) show functionality of a technology or mobile device is also a determinant of adoption despite the fact that it is always not observed (Rapudo, 2013;Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This research also identified that limited engagement of healthcare facilities in mobile health also limits the adoption of mobile phones by the elderly. This has created a division between technology and health facilities where the elderly seek medical care for their long-term illnesses ( Shahbazi, Bagherian, Sattari, & Saghaeiannejad-Isfahani, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diversos trabalhos apresentam reflexões sobre o desenvolvimento digital e as mudanc ¸as rápidas que estão sendo provocadas pela transformac ¸ão da sociedade e por crises como a do COVID-19 [Pagliari 2021, Silva et al 2021. No contexto de saúde móvel, há estudos que apontam as vantagens da utilizac ¸ão da tecnologia em diferentes grupos populacionais [Shahbazi et al 2021, Jones et al 2020] e também as oportunidades e os desafios para os campos emergentes de saúde móvel [Jones et al 2020].…”
Section: Trabalhos Acadêmicosunclassified
“…A partial solution involves digital AT resources. The potential of mobile health (mHealth) technologies to enhance healthcare accessibility, particularly for resourceconstrained demographics like older adults, is substantial in the digital era [19]. However, despite the availability of numerous health applications designed to assist older individuals [20], none were identified in the Android Google Play store or iPhone Apple App store specifically tailored to provide information about assistive technology devices for older adults with physical function disabilities in activities of daily living (ADLs) and instrumental activities of daily living (IADLs).…”
Section: Introductionmentioning
confidence: 99%